Quantification of tumour vasculature and hypoxia by immunohistochemical staining and HbO(2) saturation measurements - Fenton, B M (Nature Publishing Group, 1999)
Despite the possibility that tumour hypoxia may limit radiotherapeutic response, the underlying mechanisms remain poorly understood. A new methodology has been developed in which information from several sophisticated techniques is combined and analysed at a microregional level. First, tumour oxygen availability is spatially defined by measuring intravascular blood oxygen saturations (HbO(2)) cryospectrophotometrically in frozen tumour blocks. Second, hypoxic development is quantified in adjacent sections using immunohistochemical detection of a fluorescently conjugated monoclonal antibody (ELK3-51) to a nitroheterocyclic hypoxia marker (EF5), thereby providing information relating to both the oxygen consumption rates and the effective oxygen diffusion distances. Third, a combination of fluorescent (Hoechst 33342 or DiOC(7)(3)) and immunohistological (PECAM-1/CD31) stains is used to define the anatomical vascular densities and the fraction of blood vessels containing flow. Using a computer-interfaced microscope stage, image analysis software and a 3-CCD colour video camera, multiple images are digitized, combined to form a photo-montage and revisited after each of the three staining protocols. By applying image registration techniques, the spatial distribution of HbO(2) saturations is matched to corresponding hypoxic marker intensities in adjacent sections. This permits vascular configuration to be related to oxygen availability and allows the hypoxic marker intensities to be quantitated in situ. © 1999 Cancer Research Campaign